PENERAPAN METODE PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN MOTIVASI DAN KEMAMPUAN PEMECAHANMASALAH MATEMATIKA SISWA KELAS VIII B SMP NEGERI 3 BATUKLIANG TAHUN PELAJARAN 2016/2017 - Fahmi, Samsul; Syahrir, Syahrir; Kurniawan, Ade (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
Problems encountered in mathematics at SMP State 3 Batukliang is low motivation and problem solving skills in mathematics. Therefore this study is to describe the application of problem solving learning method that can increase motivation and problem solving skills mathematical subject matter circle in class VIII B of SMP State 3 Batukliang in the academic year 2015/2016. This research is a classroom action research (CAR) conducted in two cycles. The instrument used in this study is the observation sheet activities of teachers, students' learning motivation questionnaire and evaluation test. Based on the analysis of data obtained by the results of analysis activities of teachers in the first cycle Quite good and well, while on the second cycle well. Analysis of motivation in the first cycle Says gori high motivation and the second cycle Uncategorised very high motivation, problem-solving ability evaluation test on the first cycle with an average value of 66.5 and yet get the average value that has been set is ≥ 70 and the results of tests evaluating the ability of problem solving cycle II, the average value reached 77.85.So the results obtained from each cycle increasing. Based on these results it can be concluded that the application of learning methods Problem Solving can increase motivation and problem solving skills math class VIII B subject matter circle in the academic year 2016/2017.p